2018
DOI: 10.1177/1054773818788492
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Uncertainty in Illness Among People With Parkinson’s Disease

Abstract: People with Parkinson's disease (PD) reported to experience uncertainty because of gradually progressive disease characteristics with no cure, and variably manifesting and unpredictable symptoms. This study was designed to identify illness-related variables influencing uncertainty in PD patients and to analyze direct and indirect paths between these variables. Data were collected from 206 participants using a structured questionnaire. Path analysis revealed the direct and/or indirect effects of economic status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(66 reference statements)
0
4
1
Order By: Relevance
“…Research supports the role of social support in solving problems, providing information, and offering empathy, which can reduce illness uncertainty and improve patient outcomes. 17,18 However, depression did not affect illness uncertainty in this study. Previous research has reported an association between depression and uncertainty in patients who have had a stroke with impaired physical function and independent living limitations.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Research supports the role of social support in solving problems, providing information, and offering empathy, which can reduce illness uncertainty and improve patient outcomes. 17,18 However, depression did not affect illness uncertainty in this study. Previous research has reported an association between depression and uncertainty in patients who have had a stroke with impaired physical function and independent living limitations.…”
Section: Discussioncontrasting
confidence: 52%
“…16 There is limited research on investigating illness uncertainty in patients with UIAs who have undergone coil embolization. Studies conducted on those with Parkinson disease 17 and atrial fibrillation 18 have shown that social support is associated with lower illness uncertainty. Studies conducted on patients with chronic myeloid leukemia 13 and individuals on hemodialysis 16 indicate that higher education levels are associated with lower illness uncertainty.…”
mentioning
confidence: 99%
“…Uncertainty is a primary element in illness experiences [ 44 , 45 , 46 , 47 ] and has been described as having a negative impact on how patients cope and their disease outcomes. The evidence suggests uncertainty creates suffering in a variety of chronic illnesses [ 48 , 49 , 50 , 51 , 52 ]. ME/CFS patients can experience uncertainty on three levels.…”
Section: Me/cfs Through the Lens Of The Four-phase Modelmentioning
confidence: 99%
“…12,13 The path to diagnosis can be fraught, and effective healthcare communication is often reported as lacking. 14,15 Considering the overlap between the experiences of people with Parkinson's (PwP) and Mishel's theory of illness uncertainty, it is not surprising that high levels of uncertainty have been well established in this population, 16 including among those with younger onset (i.e. before age 50 years 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…20 Higher levels of uncertainty in PwP have also been associated with increased disease severity, lower perceived social support and decreased resilience. 16 However, a number of informal strategies have been reported to reduce uncertainty, such as focused information-gathering and increasing perceived control, 21 which could benefit from individual approaches to carefor example, allowing each patient to decide the amount of information they need at any stage. 22 Since January 2020, the threat of the COVID-19 pandemic has led to unprecedented responses globally.…”
Section: Introductionmentioning
confidence: 99%